Nutrient Value and Invitro Digestibility of Silage from Corn Forage and Indigofera Legume in Different Proportions as Nutrient Rich Feed - Mucra, Dewi Ananda; Solfan, Bakhendri; Harahap, Anwar Efendi; Juliantoni, Jepri; Adelina, Triani; Rodiallah, Muhamad; Ali, Arsyadi; Irawati, Evi; Mulianti, Mestia (Jurnal Peternakan, 2025)
The provision of ruminant feed is always influenced by the quality and quantity of forage because it is based on field grass, even though there are cultivated forages in the form of corn and indigofera legumes which are rich in nutrients and long-lasting. This research aims to assess the nutritional value, WSC and invitro digestibility of silage made from corn forage and indigofera legume in different proportions as ruminant feed. The research method used a completely randomized design with 5 treatments with 4 replications. The treatments are P1 = 100% corn forage silage (CFS); P2 = 100% indigofera legume silage (ILS); P3 = 75% CFS + 25% ILS; P4 = 50% CFS + 50%  ILS and P5 = 75% CFS + 25%  ILS. The results showed that the 100%  ILS treatment produced the highest crude protein value (P<0.05), namely 18.77%. The highest NDF value (P<0.05) was in the 100% CFS treatment and the lowest was in the 100% ILS treatment (59.47% vs 42.07%). The highest IVDMD value was found in the 100% ILS treatment, 51.23%, and the lowest was in the 100% CFS treatment, 42.63%. The conclusion of this research is that 100% indigofera legume silage produces the highest crude protein, IVDMD and IVOMD values and produces the lowest crude fiber, NDF and ADF values compared to other treatments.